An interpretive study of the factors affecting the computer literacy of secondary school students. - Newhouse, Christopher P. (Curtin University, 1987)
This study used interpretive research techniques to investigate the factors which affect the computer literacy of secondary students. The necessity that students to be prepared for life and work in a computer technology based society is widely acknowledged and has highlighted the importance of computer literacy in the high school curriculum. While the definition of computer literacy varies widely, this study defined computer literacy in terms of the knowledge, skills, and attitudes required to use computers to facilitate the completion of necessary tasks presently associated with life and required to enhance perceptions of the future use of computers. If schools are to achieve the aim of encouraging students to use computers to help them solve problems and complete tasks, it is important that educators know the factors which affect this use. This study involved an investigation of: student-computer interaction; the development of knowledge, attitudes and skills associated with computer use; and the present and perceived future utilization of computer technology.A variety of data were collected from a Year 8 class which was observed for a year as it participated in a computer literacy course. The data sources were: classroom observation; student interviews at the beginning and end of the course; an attitudes questionnaire; a background questions sheet; and student mathematics and computing class grades. In addition, to test assertions which emerged during the study, a group of Year 12 students was interviewed and data were collected from four Year 8 students who were given experience on a more state-of-the-art computer system than those used by the computer literacy class. All students involved in the study were drawn from a large, secondary senior high school situated in a middle to upper class suburb of Perth, Western Australia. From the analysis and interpretation of these data, nine assertions emerged. The assertions were classified in terms of: students; computers; learning environment; and concept development.The study found that students entering secondary school tend to have attitudes which are conducive to the use of computers. The Year 8 students enjoyed using computers and showed little anxiety in terms of computer-phobia. These students valued the use of computers and were confident in using computers when clearly instructed and not confronted by major obstacles. However, almost half of this group of students indicated a lack of confidence in some situations, particularly where they felt that they may do something to damage the computer. Almost all students were keen to learn about computers. As a result, most students in this group of Year 8 students had the attitudes most educators would recommend for enhanced learning and computer use.Three assertions were concerned with factors relating to computer hardware and software. The major obstacles to students' use of computers were: unreliability of hardware; lack of student keyboarding skills; and the use of abstract concepts in software design. Students lost confidence in using computers and undervalued their use when unreliable hardware was used. The use of a mouse by the students using the state-of-the-art computer demonstrated a means of overcoming a lack of keyboard skills. Finally, students had difficulty when using command driven software which incorporated abstract naming and design structures. Where concrete design features were incorporated in the software design, as was the case in the software used by the students on the state-of-the-art computer, students found the computers easier to use, thereby enhancing their perceptions of the value of computers.Four assertions concerned student learning environments. The environments which made significant contributions to student computer literacy were the school and home, with school being the dominant environment. Prior experience with, and learning about, computers at school and home were found to be associated with feelings of confidence and enjoyment with regard to using computers. The major influence of the home on student computer literacy was through the attitudes communicated by parents, which largely reflected their own use of computers at work. In addition, it was found that the perceptions students have of the value of the activities they are required to complete using computers, and the extent to which the computer improves the completion of those activities, are determinants of students' perceptions of the overall value of computer technology.The final assertion concerned student learning and concept development. Students entering secondary school have little knowledge of how computer systems work or how they are used. Therefore, they do not have a well developed concept of a computer and computer use. Students are amenable to the concept of computers as information processors as they develop knowledge from their interaction with computers. It was found that an important facet of this interaction concerned the degree to which students anthropomorphized computers and differentiated themselves from computers. As a result, students develop knowledge relevant to computer use with little understanding of how computer systems work.The findings of this study have implications for educational policy, teaching practice, and further research. It was recommended that schools need to develop computer literacy policies that provide students with specialist courses and, at the same time, give students experience at using computers across the curriculum. In addition, schools need to consider the purchase of more state-of-the-art computer hardware and software even where this may reduce student hands-on time. This study stressed the need for teachers to utilize and enhance the positive attitudes displayed by students towards the use of computers. At the same time, computer literacy teachers need to be concerned with the development of useful knowledge which is not based on technical knowledge of computer systems. Finally, this study recommended the need for further research to verify the findings and to further investigate student-computer interactions and student perceptions of future uses of computers.